2019
DOI: 10.1021/acssuschemeng.9b04119
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Fe3O4@Carbon Filter Media for Simultaneous Phosphate Recovery and Nitrogen Removal from Domestic Wastewater in Biological Aerated Filters

Abstract: Domestic wastewater depth processing and reclamation are essential in the alleviation of global water shortage. In this study, an innovative filter media (i.e., Fe3O4@Carbon filter media [FCM]) was synthesized and subsequently used in a biological aerated filter (BAF) for simultaneous phosphate recovery and nitrogen removal (SPN) from domestic wastewater. The performance of FCM was compared with the commercially available ceramsite (CAC). The results showed that the performance of FCMBAF was better than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The interconnectivity and uniformity of the pores were also suitable for biofilm microdistribution, where different FCM aerobic and anaerobic zones were formed. This process facilitates micro-interactions between key microorganisms and the filtration media [33].…”
Section: Resultsmentioning
confidence: 99%
“…The interconnectivity and uniformity of the pores were also suitable for biofilm microdistribution, where different FCM aerobic and anaerobic zones were formed. This process facilitates micro-interactions between key microorganisms and the filtration media [33].…”
Section: Resultsmentioning
confidence: 99%
“…Phosphate removal achieved via consumption by PAOs and HAp crystallisation on the biofilms generated in the A/OBF reactor. HAp was used by Bao et al [92] for phosphate recovery from iron(III) oxide/carbon filter media (FCM) in a biological aerated filter (BAF). Phosphate recovery was achieved by the reaction of calcium ions, phosphate ions and hydroxide ions to form and precipitate HAp on the FCM.…”
Section: Water Purificationmentioning
confidence: 99%
“…Certainly, the biomass, bioactivity, and filtration action in BAFS is highly depending on the media character, and it also significantly determines the investment of construction and operating cost. Thus, research has reported focusing on the investigation of media performance of different materials in BAFS ( Qiu et al, 2010 ; Bao et al, 2016 ; Bao et al, 2019 ), and ceramic particle was found as a favorable candidate due to its large specific surface area, high mechanical strength, and biological affinity ( Yue et al, 2009 ; Han et al, 2013 ; Yang et al, 2015 ). However, the phosphorus removal by commercial ceramsites was unfavorable as yet ( Jiang et al, 2014 ), and it is significant to propose strategies to improve its phosphorus removal.…”
Section: Introductionmentioning
confidence: 99%